An integrated mathematics/science activity for secondary students: development, implementation, and student feedback - Gentry, Abigail Rose, author; Pilgrim, Mary, advisor; Shipman, Patrick, committee member; Gloeckner, Gene, committee member (Colorado State University. Libraries, 2016)
Mathematics teachers are often challenged by their students to give reasoning for why learning mathematics is necessary. An approach to address this question is to show students the value in learning mathematics by enlightening them on the connections that mathematics has with other disciplines and the real-world applications of mathematics. Integration is a method of teaching that can be used to give students insight as to how mathematics is useful in a variety of different fields. In addition to engaging students with relevant curriculum, leading students to discover the connections between mathematics and science (among other fields) is helpful in showing students why learning mathematics is valuable. This thesis reports on my experiences in developing and implementing an integrated mathematics/science activity in a STEM Technology class at a local high school as well as discusses student feedback about the activity, about their interdisciplinary STEM Technology class, and about the integration of mathematics and science in the classroom.